The Influence of Using Visual Media Images on Arabic Language Learning Outcomes in Grade IV Students at Al-Irsyad Elementary School - Ahmad Adil Ihsan; Santi Lisnawati; Muhammad Fahri (STKIP Al Islam Tunas Bangsa dan HEPI, 2024)
This research was motivated by the low level of Arabic language learning outcomes for fourth grade students at Al Irsyad Elementary School, Bogor City. This research aims to determine the influence of visual image media on Arabic language learning outcomes. This type of research is quasi-experimental research. The population of this study was all students in Al Irsyad Elementary School, Bogor City, totaling 348 students. The sample for this research was 58 grade IV students at Al Irsyad Elementary School, Bogor City. The data collection method was carried out using a test method, namely an objective test instrument (multiple choice). The data obtained were analyzed using descriptive statistical analysis techniques and inferential statistical analysis techniques, namely the t-test. The results of this research show that there is a significant influence of the use of visual image media on the Arabic language learning outcomes of class IV students at Al Irsyad Elementary School, Bogor City based on the t-test that the Sig. (2-tailed) 0.039 < 0.05, which means that there is an influence of the use of visual image media on Arabic language learning outcomes. This can also be seen from the average score of experimental class students using visual image media, namely 86 and the average score of control group students, namely 73. So there is a significant influence of the use of image visual media on Arabic language learning outcomes for fourth grade elementary school students. Al Irsyad, Bogor City, Academic Year 2023/2024.